RELEVANSI TEOLOGI KRISTEN DALAM MENANGGAPI PERKEMBANGAN ZAMAN DI TORAJA: PERSPEKTIF IMAN, BUDAYA, DAN MODERNITAS - Sryanti Lai' Ruru; Agustina Paseru, Bimbang Randa, Bersa Lidia Limbong, Sinrayanti Ewanan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Christian theology in Toraja experiences complex dynamics along with the development of the times. This article discusses how the church and Christian society in Toraja balance Christian values and local culture, especially in traditional practices such as Rambu Solo' and Rambu Tuka'. The challenges of globalization and modernization also have an impact on the understanding of faith, especially for the younger generation who are exposed to secular thinking and the influence of social media. The church in Toraja responds to these changes by developing contextual theological strategies, flexible pastoral care, and the use of technology in spreading the gospel. With collaboration between church leaders, academics, and local communities, Christian theology in Toraja is expected to continue to develop without losing its essence. This article highlights the importance of balancing traditional values and innovation to ensure the relevance of Christian theology in the future